ANALYSIS OF COFFEE SHOP DISTRIBUTION PATTERNS IN BUKITTINGGI CITY - RAHMAT, MEIGI; Mariya, Sri (JURNAL BUANA, 2025)
This study aims to analyze the pattern of distribution of Coffee Shop business locations in Bukittinggi City by conducting a spatial study and analyzing the characteristics of the distribution pattern of Coffee Shops based on the spatial structure in the City of Bukittinggi. The sampling technique was carried out using the Total Sampling technique for 25 Coffee Shop point locations. The data collection technique used is observation and documentation techniques. The results of this study showed th at the coffee shop distribution pattern in Bukittinggi City obtained a T score of 0.99 and a z-score of 0.59, meaning that the distribution of Coffee Shop points in Bukittinggi City is spread unequally (random pattern). . The results of this study show that the social structure of coffee shops in the city of Bukittinggi is spread unequally. Most of them are in the Guguak Panjang sub-district. In terms of roads, there are many on local roads. In the Coffee Shop area in Bukittinggi City there are many trade and service areas.